Fabrication, in-vitro characterization, and enhanced in-vivo evaluation of carbopol-based nanoemulsion gel of apigenin for UV-induced skin carcinoma - Manmohan S. Jangdey; Anshita Gupta; Swarnlata Saraf (Taylor & Francis Group, 2017)
The aim of this study was to develop a potential novel formulation of carbopol-based nanoemulsion gel containing apigenin using tamarind gum emulsifier which was having the smallest droplet size, the highest drug content, and a good physical stability for Skin delivery. Apigenin loaded nanoemulsion was prepared by high speed homogenization method and they were characterized with respect to morphology, zeta potential, differential scanning calorimeter study, and penetration studies. In-vitro release studies and skin permeation of apigenin loaded nanoemulsion by goat abdominal skin was determined using Franz diffusion cell and confocal laser scanning microscope (CLSM). The cytotoxicity of the reported formulation was evaluated in HaCaT Cells (A) and A431 cells (B) by MTT assay. The nanoemulsion formulation showed droplet size, polydispersity index, and zeta potential of 183.31 nm, 0.532, and 31.9 mV, respectively. The nanoemulsions were characterized by TEM demonstrated spherical droplets and FTIR to ensure the compatibility among its ingredients. CLSM showed uniform fluorescence intensity across the entire depth of skin in nanocarriers treatment, indicating high penetrability of nanoemulsion gel through goatskin. The nanoemulsion gel showed toxicity on melanoma (A341) in a concentration range of 0.4-2.0 mg/ml, but less toxicity toward HaCaT cells. The carbopol-based nanoemulsion gel formulation of apigenin possesses better penetrability across goatskin as compared to marketed formulation. Hence, the study postulates that the novel nanoemulsion gel of apigenin can be proved fruitful for the treatment of skin cancer in near future.